New paradigm of the medical audit: multidisciplinary or transdisciplinary approaches? - Biryukov, V. S.; Badiuk, N. S. (Journal of Education, Health and Sport, 2017)
The study is devoted to formation a new paradigm in relation the essence of medical audit. Using the example of requirements international quality standards ISO 90001: 2015 and GCP, it is shown that disciplinary and multidisciplinary approaches are progressive steps in implementing the quality policy in medical services, but they are unable to overcome the fundamental drawback - fragmentation the system. Thus, the audit quality management system in health care institution, in accordance with the ISO 9001 standard, does not allow assessing the quality of procedures performed by medical personnel, the adequacy of diagnostic and therapeutic actions in relation to nosological units, the comparative efficiency and effectiveness methods of treatment and diagnostics used. In its turn, the clinical audit by GCP standard is not able to detect defects work of support services, various risks accompanying medical activities, reveal the degree of patient satisfaction with medical services and provide evidence of economic viability to partners. Economic audit, in turn, is not able to give an idea of competence level of management and medical personnel in medical institution. A more complete picture activity a medical institution can be obtained through a medical audit involving an interdisciplinary approach in which a new system-forming concept is formed on the basis of integration data from various disciplinary methods.